Ownership and Pay in Britain - Andrew Pendleton; Alex Bryson; Howard Gospel (Institute for the Study of Labor (IZA), 2015)
Drawing on principal-agent perspectives on corporate governance, this paper examines whether employees' hourly pay is linked to ownership dispersion. Using linked workplace-worker data from the British Workplace Employment Relations Survey (WERS) 2011, we find average hourly pay is higher in dispersed ownership workplaces. The raw gap of 30 log points falls to 8 log points when we control for differences in worker and workplace characteristics. The premium is constant across most of the wage distribution, but falls a little at the 90th percentile to become statistically non-significant. This contrasts with earlier papers which indicate that higher level employees are the primary beneficiaries of higher pay from dispersed ownership.
Keywords: G3; G32; G31; 330; ownership structure; corporate governance; principal agent; pay